Des espaces-fantômes de Marie Darrieussecq – “faire entendre le son que rendent d’autres espaces” - Gyimesi, Timea (Verbum – Analecta Neolatina, 2014)
This study aims to analyse the use of space inMarie Darrieussecq’s novels. Space will be analysed in the framework of an esthetic programme which falls within chaos theory and the geophilosophy of Gilles Deleuze and Félix Guattari. This framework seems particularly useful at unfolding Darrieussecq’s outlandish haptic “spacephantoms” (land, mind, waves, etc.) as well as her becomings (fool, baby, dead people, sow, etc.).